Etnobotânica e biodiversidade: correspondências entre saberes populares e espécies medicinais no SUS em Sorocaba/SP - Branco, Milene Souza (Universidade Federal de São Carlos, 2025)
This dissertation analyzes the correspondence between popular knowledge about the therapeutic use of medicinal plants in Sorocaba/SP and the species existing in gardens and flowerbeds of Basic Health Units (UBS) in this municipality. The research was developed in two complementary stages: botanical survey and ethnobotanical investigation. In the first, 49 species were recorded in three health units, of which 34.7% are native to Brazil, 49% are exotic, and 16.3% are naturalized, 20 of which are included in the National List of Medicinal Plants of Interest to the SUS (Renisus). In the second, carried out through interviews and guided tours with six interlocutors recognized as holders of knowledge about plants, 81 species belonging to 44 botanical families were identified, showing that the use of plants transcends their biochemical function, constituting a symbolic and cultural web that integrates body, territory, and spirituality. The study also revealed 20 species common to both health units and the Brazilian National List of Medicinal Plants (Renisus), and 28 species common to both popular knowledge and Renisus, showing that some of the species on the official SUS list (Renisus) are known by the population and are cultivated in health units. On the other hand, popular knowledge recorded 42 exclusive species (not cited in Renisus and notcultivated in health units), 35 of which are native or naturalized, demonstrating that popular knowledge can contribute to expanding the Renisus list. The study also highlights the still largely unexplored potential of investigating the dynamics of knowledge about medicinal plants in urban contexts, broadening the perspective of ethnobotany beyond rural and traditional communities.
Ethnobotany and biodiversity: correspondences between popular knowledge and medicinal species in the Brazilian Unified Health System in Sorocaba/SP
Etnobotánica y biodiversidad: correspondencias entre conocimientos populares y especies medicinales en el Sistema Único de Salud en Sorocaba/SP
Keywords: Etnobotânica; Plantas Medicinais; Sistema Único de Saúde; Ethnobotany; Medicinal Plants; Unified Health System; OUTROS; 3. Saúde e Bem-Estar; 11. Cidades e Comunidades Sustentáveis; 13. Ação contra a Mudança Global do Clima